Respuesta :

Answer:

[tex]r=\frac{-a+p}{a+p}[/tex]

Step-by-step explanation:

[tex]-pr+p=ar+a[/tex]

[tex]-ar-pr+p=a[/tex]

[tex]-ar-pr=a-p[/tex]

[tex]r(-a-p)=a-p[/tex]

[tex]r=\frac{-a+p}{a+p}[/tex]

Hi1315

Answer:

[tex]r = \frac{p - a}{(p + a)} [/tex]

Step-by-step explanation:

[tex]p = \frac{a(1 + r)}{(1 - r)} \\ p(1 - r) = a(1 + r) \\ p - pr = a + ar \\ p - a = pr + ar \\ p - a = r(p + a) \\ \frac{p - a}{(p + a)} = \frac{r(p + a)}{(p + a)} \\ \frac{p - a}{(p + a)} = r[/tex]

hope this helps

brainliest appreciated

good luck! have a nice day!

ACCESS MORE